Sensualism & Its Influence on Muslim Scholars - Faqih, Adbul Jalil (Journal of Social Sciences - Kabul University, 2022)
Scholars have always taken two paths to research the humanities, as well as to find the hidden Truths beyond this creation, and have been confronted by two opposing procedure called sensualists and rationalists. Sensuality, which denies intellects and considers the unseen and the metaphysic as imagination, does not pay attention to rational concepts, but only considers the result of experience and test as science and knowledge, and considers true cognition to be limited to sensory cognition. This notion has caused many religious beliefs, which are intellectual or metaphysic matters and constitute a large part of religious beliefs, to lose their meaning and sanctity, and considered as visionary.